Biosorption of Cd (II), Cu (II), Fe (III) And Pb (II) from water system using moringa oleifera leaves - Sabreen, Ramzi Alfarra (2015)
This study was an attempt to use Moringa oleifera leaves as a natural alternative for synthetic sorbents to reduce the presence of Cd (II), Cu (II), Fe (III) and Pb (II) from water. In this study synthetic water was used to determine the optimum conditions for Cd (II) removal from synthetic water using the biosorbent as first stage of the study. The effect of biosorbent dosage and particle size, contact time, and pH as well as the initial concentration of Cd (II) was studied. Atomic Absorption Spectroscopy (AAS) was used to monitor the experimented ions’ concentration before and after using the biosorbent. Fourier Transform Infrared Spectroscopy (FTIR) was used to monitor biosorbent structure changes before and after loading with Cd (II). The parameters studied were biosorbent dosage 2 to 20 g/l, contact time used was from 2 min to 120 min, biosorbent particle sizes used were 2 mm, 1 mm, 500μm, 250μm, and < 250μm, pH ranges started from 4-10, and the Cd (II) initial concentrations were 1, 3, 5, and 7 ppm. Results revealed that the optimum parameters to reduce 81% of Cd (II) were 12 g/l of biosorbent, 60 min of contact time, <250 μm biosorbent particle sizes with Cd (II) initial concentration of 1 ppm and 50 NTU. The optimized parameters obtained in the study for Cd (II) removal, were applied for Fe (III), Pb (II) and Cu (II) removal, as an attempt to experiment the effect of the optimum parameters of Cd (II) on the other heavy metals. Results showed that the removal efficiency of Moringa oleifera leaves was 81% for Cd (II), 78% for Cu (II), 63.6% for Pb (II) and 62% for Fe (III). It was clear that the achieved optimum conditions give the best removal efficiency percentage on Cd (II) removal. Student t-test results showed that the investigated parameters have an effect on Cd (II) removal with p values <0.05. Biosorption kinetic data were properly fitted with the pseudo-second-order kinetic model. FTIR presented changes in the peaks of the main functional groups and fingerprint area of Moringa oleifera leaves after Cd (II) adsorption experiments; results of FTIR indicated the reactivity of Cd (II) with the biosorbent chemical ingredients and its surface. The SEM results showed that there were differences on the morphological characteristics of the biosorbent, which also indicates the binding process of Cd (II) on the Moringa oleifera leaves. Again, the optimum condition was applied on drainage water, and showed removal efficiency of 83.6% for Cd (II), 73% for Cu (II), 65% for Pb (II) and 52% for Fe (III). Although the results of Moringa oleifera leaves on other heavy metals showed that Moringa oleifera as a biosorbent could reduce the other metals with less percentages which could suggest that Moringa oleifera is a good biosorbent for all the investigated ions generally and Cd (II) particularly. As a conclusion, Moringa oleifera leaves can be a potential and effective, low cost and environmentally friendly biosorbent for the removal of Cd (II) from water systems and reduce the Cu (II), Pb (II) and Fe (III) as well.